Swift in the cloud - Williamson, Leigh; Ponzo, John; Bohrer, Patrick; Olivieri, Ricardo; Weinmeister, Karl; Kallner, Samuel (John Wiley & Sons, 2017)
Write and run Swift language programs in the Cloud Written by the team of developers that has helped bring the Swift language to Cloud computing, this is the definitive guide to writing and running Swift language programs for cloud environment